Aplikasi Pengambilan Keputusan Menggunakan Metode Additive Ratio Assessment (ARAS) Dalam Menentukan Kepuasan Pelanggan Ojek Online - Dwi Syaputra; Adidtya Perdana; Rizko Liza (UIN Sumatera Utara, 2021)
Online ojek is a transformation from a base ojek that uses a motorbike as a means of transportation. Online motorcycle taxis are the latest public transportation trend in society. This can be a transportation solution in Indonesia, especially in big cities that experience congestion. But unfortunately now there are still online motorcycle taxi drivers who do not care about the quality of service they provide to customers. Therefore, a system is needed that can determine the level of customer satisfaction with online motorcycle taxi services based on predetermined criteria. This study uses the Decision Support System concept using the ARAS method. ARAS method is a method based on the intuitive principle that the alternative must have the largest ratio to produce the optimal solution. The Additive Ratio Assessment (ARAS) method performs a ranking by comparing the value of each criterion on each alternative by looking at the weight of each to get the ideal alternative. There are ten alternatives in the study, namely, Driver A, Driver B, Driver C, Driver D, Driver E, Driver F, Driver G, Driver H, Driver I, Driver J.Keywords: Decision Support System, Customer Satisfaction, Online Ojek Driver, ARAS Method